ESSCA results with the baseline series, 2002–2012: p‐phenylenediamine. (19th May 2016) - Schuttelaar, Marie‐Louise A.; Vogel, Tatiana A.; Rui, Francesca; Kręcisz, Beata; Chomiczewska‐Skora, Dorota; Kieć‐Świerczyńska, Marta; Uter, Wolfgang; Larese Filon, Francesca
Summary: Background: Allergic contact dermatitis caused by p ‐phenylenediamine (PPD) is common among all age groups and both sexes. Monitoring of prevalence and intensity of sensitization is important. Objective: To evaluate contact allergy to PPD in Europe, and to compare reaction intensities in different European regions. Methods: Data collected by the European Surveillance System on Contact Allergies (ESSCA) network between 2002 and 2012 from 12 European countries were analysed regarding prevalence, grading of positive reactions to PPD, and relevance. Results: A total of 99 926 PPD‐positive patients from 63 departments were included for analysis. The overall (2002–2012) prevalence of PPD sensitization in Europe is ∼4%. Stratified for country, the highest overall standardized prevalence was found in Lithuania, and the lowest in Slovenia. The prevalence of PPD sensitization did not decline over the years. In the southern European countries, higher numbers of strong and extremely strong reactions were registered. The clinical relevance of PPD sensitization varied from half to three‐quarters. Conclusion: The prevalence of PPD sensitization has not changed over time. Strong and extremely strong patch test reactions are seen more often in the South, probably because of the higher number of PPD‐containing hair dye products.